Dual-resonant polarization-independent and wide-angle metamaterial absorber in X-band frequency - Ayop, Osman (Springer Verlag, 2016)
This paper presents the analysis of dual-resonant polarization-independent metamaterial absorber with wide operating angle in X-band frequency. Two circular rings with different radius are used as resonating elements. The resonating elements which are made by copper are printed on two surfaces (top and bottom) of dual-layer FR4 substrate. At the middle layer, a full copper layer is placed. The performance of dual-resonant circular ring metamaterial absorber is observed using CST software. From simulated result, the proposed structure achieves high absorbance, which is 96.41 and 93.61 % at 9 and 11 GHz, respectively, for normal incident wave. For measurement, the resonant frequencies are found at 9.39 and 11.63 GHz with absorbance of 99.07 and 83.70 %, respectively. Then, the structure is also simulated for oblique incident angles. It is observed that the operating angle of the proposed metamaterial absorber is 70° for TE modes and 67° for TM modes. Measurement for oblique incident angle is done to validate the simulated result. Mutual agreement is achieved between simulated and measured result with slight frequency shift and ripples.